Photocatalytic oxidation dynamics of acetone on TiO 2: tight-binding quantum chemical molecular dynamics study - Lv, Chen; Wang, Xiaojing; Agalya, Govindasamy; Koyama, Michihisa; Kubo, Momoji; Miyamoto, Akira (Applied surface science, 2005)
The clarification of the excited states dynamics on TiO 2 surface is important subject for the design of the highly active photocatalysts. In the present study, we applied our novel tight-binding quantum chemical molecular dynamics method to the investigation on the photocatalytic oxidation dynamics of acetone by photogenerated OH radicals on the hydrated anatase TiO 2 surface. The elucidated photocatalytic reaction mechanism strongly supports the previous experimental proposal and finally the effectiveness of our new approach for the clarification of the photocatalytic reaction dynamics employing the large simulation model was confirmed.